Case report: Primary infection of conjunctival histoplasmosis mimicking a large conjunctival neoplasm in an immunosuppressed patient - Lam, Jonathan; Hussain, Rumana; Coupland, Sarah E.; Heimann, Heinrich (Frontiers in Medicine, 2024)
We report a rare case of rapidly growing and large conjunctival histoplasmosis lesion in an immunosuppressed West African woman in her 80s, affecting her only eye. The patient was on immunosuppressive medications for renal transplant and had been previously treated for presumed systemic histoplasmosis with itraconazole over 5 years ago. Despite previous treatment, she presented with a large conjunctival lesion confirmed to be histoplasmosis after excisional biopsy. The lesion had been noted to grow over a 2-week period, causing significant visual impairment. Following comprehensive systems review and investigation, the conjunctiva was identified as the sole site of infection. This case underscores the rarity of sight-threatening histoplasma infection in the conjunctiva of an immunosuppressed individual. Conjunctival histoplasmosis lesions are infrequently reported, with even fewer cases documented as originating primarily in this location